INTERACTIVE ENGAGEMENT STRATEGIES FOR ONLINE LEARNING: NOMINAL GROUP TECHNIQUE APPROACH FOR HIGHER EDUCATION STUDENTS - Md Hamzaimi Azrol bin Md Baharudin; Mohd Fakri Muda; Amminudin Ab Latif; Wan Zukri Wan Abdullah; Mohd Razmi Zainudin; Rasyad Afif Ibrahim (Journal of Islamic, Social, Economics and Development, 2023)
The online learning environment is a modern educational paradigm that leverages digital technologies and the internet to deliver educational content and facilitate learning experiences in a remote environment. This mode of learning has gained significant traction, especially in recent years, owing to its flexibility, accessibility, and convenience. However, online learning presents challenges that require careful consideration. Students engaged in online learning need to exhibit a high level of self-motivation and discipline, as the absence of physical classroom settings demands proactive time management and personal responsibility. The lack of face-to-face interactions can potentially lead to feelings of isolation, emphasizing the importance of building virtual communities and communication channels to maintain engagement and actively participation. The aim of this paper is to see the views and recommendations of experts in dealing with active participant and engagement in online learning environment among students. Then make the conclusions and recommendations of best practice of active participant and engagement strategies in online learning based on expert recommendations. The findings of this study highlight several online learning strategies that received the highest ranking from experts, including clear communication, interactive contents, collaborative projects, real-world relevance, polls and surveys, storytelling and case studies, instructors’ active presence, and reflective activities. In future research, it is advisable for investigators to delve into a more comprehensive examination of the efficacy of student engagement in online learning through the integration of multiple strategies. Furthermore, the forthcoming study should also address the preparedness of new educators in adapting to online learning environments, as well as their proficiency in information technology literacy.